X-(-7)=-10 X+(-13)=20 2(x+3)-5=-13 x-8=-15 3(2x-4)+(-9)=-12 2(6-3x)-(-7)=-15

X-(-7)=-10

X+(-13)=20

2(x+3)-5=-13

x-8=-15

3(2x-4)+(-9)=-12

2(6-3x)-(-7)=-15

2 bình luận về “X-(-7)=-10 X+(-13)=20 2(x+3)-5=-13 x-8=-15 3(2x-4)+(-9)=-12 2(6-3x)-(-7)=-15”

  1. x – (-7) = -10
    => x = -10 -7
    => x = -17
    Vậy x = -17
    ——-
    x + (-13) = 20
    => x = 20 + 13
    => x = 33
    Vậy x = 33
    ——
    2(x + 3) – 5 = -13
    => 2(x + 3) = -13 + 5
    => 2(x + 3) = -8
    => x + 3 = -8 : 2
    => x + 3 = -4
    => x = -4 – 3
    => x = -7
    Vậy x = -7
    ———-
    x – 8 = -15
    => x = -15 + 8
    => x = -7
    Vậy x = -7
    ———
    3(2x – 4) + (-9) = -12
    => 3(2x – 4) = -12 + 9
    => 3(2x – 4) = -3
    => 2x – 4 = -3 : 3
    => 2x – 4 = -1
    => 2x = -1 + 4
    => 2x = 3
    => x = 3/2
    Vậy x = 3/2
    ———
    2(6 – 3x) – (-7) = -15
    => 2(6 – 3x) = -15 – 7
    => 2(6 – 3x) = -22
    => 6 – 3x = -22 : 2
    => 6 – 3x = -11
    => 3x = 6 + 11
    => 3x = 17
    => x = 17/3
    Vậy x = 17/3
     

    Trả lời
  2. x-(-7)=-10
    x=(-10)+(-7)
    x=-17
    _Vậy : x=-17.
    ——-
    x+(-13)=20
    x=20-(-13)
    x=33
    _Vậy : x=33.
    ——-
    2(x+3)-5=-13
    2x+6=-13+5
    2x+6=-8
    2x=-8-6
    2x=-14
    x=-14:2
    x=-7
    _Vậy : x=-7.
    ——-
    x-8=-15
    x=-15+8
    x=-7
    _Vậy : x=-7.
    ——-
    3(2x-4)+(-9)=-12
    6x-12=-12-(-9)
    6x-12=-3
    6x=-3+12
    6x=9
    x=9/6
    x=3/2
    _Vậy : x=3/2 .
    ——-
    2(6-3x)-(-7)=-15
    12-6x=-15+(-7)
    12-6x=-22
    6x=12+22
    6x=34
    x=34/6
    x=17/3
    _Vậy : x=17/3
     

    Trả lời

Viết một bình luận

Câu hỏi mới